"State-of-Art" paper of the Italian Working Group on Atherosclerosis: Preclinical assessment of early coronary atherosclerosis. (1st July 2016) - Madonna, Rosalinda; Selvaggio, Stefano; Selvaggio, Giancarlo; Coronelli, Maurizio; Cocco, Nino
Abstract: Although the early diagnosis and treatment for acute myocardial infarction have improved over the past decades, the morbidity and mortality from coronary artery disease (CAD) remain significant in Europe and worldwide. It is estimated that the majority of people in the developed countries who die suddenly from CAD, have no prior manifestation of disease, and the majority of these individuals are not considered to be at high risk. Accurate identification of individuals at risk of such events before the clinical manifestations is therefore required. This "State-of-Art" paper of the Italian Working Group on Atherosclerosis aims to i. provide an overview of both the traditional and emerging non-invasive imaging techniques used to detect early atherosclerosis in the general population with moderate cardiovascular risk; ii. identify the rationale for screening asymptomatic patients with preclinical atherosclerotic lesions and the optimal algorithm that should be used to detect them; iii. discuss the future directions of atherosclerosis research, with special focus on nanotechnology, aimed at early identification and treatment of low- and intermediate-risk patients. Highlights: Early diagnosis and treatment for acute myocardial infarction is still challenging. This "State-of-Art" paper aims to: Provide an overview of non-invasive imaging techniques used to detect early atherosclerosis Identify the rationale for screening asymptomatic patients Discuss the future directions of atherosclerosis research